Masonry interlocking Concrete Earth Blocks (CEB) confined in a reinforced concrete structure - Brizuela, Eduardo Enrique (2020)
From the acquisition of a press for Concrete Earth Blocks (CEB) that is in disuse and as part of the project of a workshop for a small construction company, this research is carried out on the production process of these Interlocked Concrete Earth Blocks, the selection of suitable soils and stabilizers selected for its elaboration, the execution of masonry with this type of block, the study of its production costs and comparison with the costs of other masonry.